Aplikasi Eco-enzym untuk Pemurnian Air Terkontaminasi dan Budidaya Tanaman Obat Keluarga: Application of Eco-enzymes for Purification of Contaminated Water and Cultivation of Family Medicinal Plants - Probowati, Wiwit; Wijayanti, Suprihatin; Rika, Rika; Pramesti, Indah; Isnaini, Febriana Nur; Nisa, Neny Fahrun (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Increased water pollution due to industrial, household, and agricultural waste has triggered the need for environmentally friendly technologies for water purification. Eco-enzyme, a solution fermented from various kinds of fruit and vegetable kitchen waste with the addition of sugar and water is recognized to have anti-bacterial and anti-fungal properties effective in decomposing toxic substances and improving water quality. Utilization of waste enzymes is emerging as a viable strategy to treat contaminated water as well as organic fertilizer in the cultivation of family medicinal plants. This training activity on eco-enzyme making and pouring was carried out in the framework of community service activities and the 2024 eco-enzyme festival. Training on making eco-enzymes was carried out using socialization and demonstration methods. Then the finished eco-enzymes were poured into the river behind the campus of 'Aisyiyah University Yogyakarta and watered in the cultivation of Family Medicinal Plants in Sidoagung village, Godean sub-district, Sleman. Based on the evaluation of the activity, participants were very enthusiastic about understanding new knowledge and were able to practice the results of making eco-enzymes. In addition to creating a clean environment, pouring eco-enzymes into the river reduces the contamination of pollutants. In addition, the application of eco-enzymes to the cultivation of family medicinal plants can function as a liquid organic fertilizer that fertilizes the soil and optimizes plant growth.